Report of the Outcome of 6-year Blood Blister-Like Aneurysm Treatment Using Clipping Technique: A Single-Center Experience - Ahrari, Iman; Rahmanian, Abdelkarim; Eqbal, Meisam; Ghavipisheh, Mahsa; Namjoo-Moghadam, Ali; Ahrari, Sobhan; Hosseini, Ehsan Mohammad; Jamali, Mohammad (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Blood blister-like aneurysms (BBA) are rare vascular lesions with challenging treatment. While direct surgery has been the primary technique for treating BBA, there has been a shift toward endovascular methods in recent years. This article presents a retrospective case series of patients treated with direct surgery at our center over a 6-year period.Patients who underwent surgery for BBA from 2014 to 2019 were evaluated. Data on surgical procedures, complications, and clinical outcomes were obtained from patients' medical records. Additionally, patients were contacted to provide updates on their treatment outcomes.A total of 17 patients were treated for BBA during the study period. All cases presented with subarachnoid hemorrhage and were treated using the clipping method. Intraoperative rupture occurred in 11 patients. Additionally, internal carotid artery sacrificing was done in five patients due to avulsion during surgery. Of these 17 patients, 11 (64.7%) had favorable outcomes following surgery, while the mortality rate was 29.4% (5 patients).The rate of favorable outcomes and mortality associated with the direct surgery technique at our center was comparable to results from other centers. Further studies are required to determine the optimal method for treating BBA.
Keywords: aneurysm; blood blister-like aneurysm; direct clipping; internal carotid artery; subarachnoid hemorrhage